Wasathiyyah in Tafsir: A Semiotic Study of the Meaning of Moderation in the Qur'an - Sulaiman Ibrahim; Moh. Azwar Hairul (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2024)
This study examines the meaning of moderation in the Quran using a semiotic approach, specifically through the interpretations of Hamka and Quraish Shihab on verses related to the concept of wasatiyyah. Wasatiyyah, which is interpreted as "the middle path," emphasizes balance between this world and the hereafter, and steers people away from extremism. This study focuses on the interpretation of Surah Al-Baqarah verses 143 and 238, Surah Al-Maidah verse 89, Surah Al-Qalam verse 28, and Surah Al-Adiyat verses 4-5, analyzing the differences in interpretation between the two exegetes using Charles Sanders Peirce's theory of semiosis. The results of the study show that moderation in Islam, as reflected in the concept of wasatiyyah, prioritizes balance between spiritual and material aspects and encourages the community to avoid two extremes that have the potential to destroy social harmony. Moderation is also applied in other aspects of life, including in Islamic religious education, where openness, compassion, and flexibility are the main principles in shaping the climate of communication in Islam.